DETERMINATION OF CONCENTRATION OF HEAVY METALS AFTER MORDANT DYEING WITH VEGETABLE DYES IN WOOL FIBERS STRUCTURE - N. A. Shagina (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
This paper describes a method for quantifying the content of heavy metal ions on the example of mordant dyeing with vegetable dyes thistle. As mordant used copper salts. The experimental results show that the maximum allowable concentration of copper ions in the structure of the wool fiber are within normal limits. It is shown that the methods of coloring wool fabric does not affect the mechanical properties of the fiber.